Integrating Product Design and Entrepreneurship Education: A Stimulant for Enterprising Design and Engineering Students in South Africa. (2015) - Odora, R.J.
Abstract: This paper presents the effects of product design projects on Design and Engineering students' innovation and entrepreneurial skills. Design project, among other things, focuses students' attitudes and interests towards entrepreneurship. Pre-survey and post-survey tests were administered to students during the introduction of product design project and after the completion of the design project. Five students were randomly selected and interviewed after the completion of the product design project. Analysis of the surveys indicates that students did not only improve their ability to design market-driven products but also learnt key entrepreneurial skills such as appreciating product design as a business niche area, conducting market research and identifying customer's needs and wants. The interview results indicate that product design projects contributes to the development of positive attitudes and interest in entrepreneurship and has a significant effects on enterprising Design and Engineering students in South Africa.